Geometry-induced electrostatic trapping of nanometric objects in a fluid. - Krishnan, M; Mojarad, N; Kukura, P; Sandoghdar, V (2010)
The ability to trap an object-whether a single atom or a macroscopic entity-affects fields as diverse as quantum optics, soft condensed-matter physics, biophysics and clinical medicine. Many sophisticated methodologies have been developed to counter the randomizing effect of Brownian motion in solution, but stable trapping of nanometre-sized objects remains challenging. Optical tweezers are widely used traps, but require sufficiently polarizable objects and thus are unable to manipulate small macromolecules. Confinement of single molecules has been achieved using electrokinetic feedback guided by tracking of a fluorescent label, but photophysical constraints limit the trap stiffness and lifetime. Here we show that a fluidic slit with appropriately tailored topography has a spatially modulated electrostatic potential that can trap and levitate charged objects in solution for up to several hours. We illustrate this principle with gold particles, polymer beads and lipid vesicles with diameters of tens of nanometres, which are all trapped without external intervention and independently of their mass and dielectric function. The stiffness and stability of our electrostatic trap is easily tuned by adjusting the system geometry and the ionic strength of the solution, and it lends itself to integration with other manipulation mechanisms. We anticipate that these features will allow its use for contact-free confinement of single proteins and macromolecules, and the sorting and fractionation of nanometre-sized objects or their assembly into high-density arrays.